The Analysis of High-Order Thinking Skills in EFL Textbooks of Senior High School: (Content Analysis of EFL Textbooks) - Islamiati, Izzatuddini; As'ari; Nur Arifin, Moh. (English Education, Linguistics, and Literature Journal, 2025)
This research focused on conducting a content analysis of the Erlangga English Textbook “Pathway” used in the first senior high school. The study aimed to evaluate the content alignment within the textbook. Employing a descriptive qualitative approach, data were gathered from the “Pathway” textbook authored by Th. M. Sudarwati and Eudia Grace, edited by Yuniar Widiastuti and Dwi Wahyu Priyanto, and published by Erlangga Publisher in 2016. Designed for Senior High School and MA Grade X, the textbook features 118 essay reading questions, among which 107 questions (90.7%) emphasize lower-order thinking skills, and 11 questions (9.3%) focus on higher-order thinking skills (HOTS). Specifically, within the HOTS questions, 2 questions (1.7%) pertain to analytical skills, and 9 questions (7.6%) relate to evaluative skills, with no questions dedicated to creative skills. This analysis concludes that the reading exercises in the Erlangga English Textbook “Pathway” are deficient in Higher Order Thinking Skills, with a predominant emphasis on lower-order thinking skills. Among the 11 HOTS questions identified, the evaluating skill emerges as the most frequently utilized within the reading exercises of this textbook.